2013
DOI: 10.1017/s0959259813000208
|View full text |Cite
|
Sign up to set email alerts
|

HIV and ageing: what the geriatrician needs to know

Abstract: SummaryThe transformation of human immunodeficiency virus (HIV) from a rapidly fatal disease to a chronic manageable illness has resulted in annual increases in the numbers of people living with HIV. The HIV cohort is therefore ageing, with numbers of older adults with HIV climbing, through both prolonged survival and late acquisition of the disease. Associated with ageing is an accumulation of HIV-associated non-AIDS related co-morbidities, creating a complex patient group affected by multi-morbidity along wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 127 publications
(154 reference statements)
0
6
0
3
Order By: Relevance
“…This study has shown examples of geriatrician involvement as has other literature . There is also an increasing literature aimed at informing geriatricians of the issues pertinent to ageing in PLWH [).…”
Section: Discussionmentioning
confidence: 68%
“…This study has shown examples of geriatrician involvement as has other literature . There is also an increasing literature aimed at informing geriatricians of the issues pertinent to ageing in PLWH [).…”
Section: Discussionmentioning
confidence: 68%
“…A particular concern in this population regards MM as a predictor care complexity and polypharmacy increasing the cost of clinical management[ 17 ]. Moreover polifarmacy rises risks of pharmacological interactions and medical errors[ 18 20 ]. Ageing and chronic HIV infection can also both contribute to subclinical changes, including atherosclerosis, bone mineral density, and changes in T cell function.…”
Section: Discussionmentioning
confidence: 99%
“…Sejak highly active anti-retroviral therapy (HAART) diperkenalkan pada tahun 1996 dan dimulai terapi anti retroviral kombinasi, pasien HIV yang terdiagnosis awal dan mendapat terapi antiretroviral dapat hidup seperti orang normal pada umumnya. 1 Pada penelitian yang dilakukan oleh Greene, dkk. 2 ditemukan rentang waktu terpanjang dari pasien terdiagnosis HIV hingga saat penelitian dilakukan mencapai 21 tahun.…”
Section: Pendahuluanunclassified
“…Untuk mencapai successful ageing, seorang individu harus menjaga kondisi fisik, mental dan diterima secara sosial. 1 Pasien geriatri dengan HIV mengalami kemunduran fisik serupa dengan pasien tanpa HIV yang berusia 20-30 tahun lebih tua. Ada beberapa faktor yang menyebabkan terjadinya kondisi tersebut.…”
Section: Successful Ageingunclassified
See 1 more Smart Citation